1965
DOI: 10.1515/znb-1965-0708
|View full text |Cite
|
Sign up to set email alerts
|

Die Synthese von Derivaten des Hexadeuterobenzols

Abstract: Aus Hexadeuterobenzol wurden in successiver Umwandlung 15 deuterierte Verbindungen synthetisiert und bezüglich ihres D-Gehaltes durch IR-, NMR-, ESR- und Massen-Spektroskopie charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1967
1967
1997
1997

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An esr signal for I was observed when 2,4,6-tri-ibutylmagnesium bromide was treated with oxygen or quiñones (232). The synthesis of hindered phenols and the corresponding phenoxy radicals which contain various isotopes has been described in several papers (86,87,231,273,277,279,281).…”
Section: Othersmentioning
confidence: 99%
“…An esr signal for I was observed when 2,4,6-tri-ibutylmagnesium bromide was treated with oxygen or quiñones (232). The synthesis of hindered phenols and the corresponding phenoxy radicals which contain various isotopes has been described in several papers (86,87,231,273,277,279,281).…”
Section: Othersmentioning
confidence: 99%
“…This work was supported by the Deutsche Forschungsgemeinschaft and the Fonds der Chemischen Indusirie. -Part 4: R. W. Saalfmnk, E. Ackermann, H. WinkIer, R anion, and the acceptor substituent (A) is replaced by a stabilized cation, then one obtains a dipolar carbene (2) which can also be regarded as allene (3). We have now found that such donor/acceptor-substituted allenes are likewise ambiphilic, i. e. can react at the central atom C2 both electrophilically as well as nucleophilically.…”
Section: E Niecke H Zorn B Krebs C Henkelmentioning
confidence: 93%
“…Ambiphilic carbenes, e. g. chloro(methoxy)carbene, exhibit electrophilic and nucleophilic selectivity, respectively, towards electronrich and electron-deficient olefins"]. If the donor substituent (Do) in an ambiphilic carbene (2) is replaced by a stabilized [' I Univ.- 3) anion, and the acceptor substituent (A) is replaced by a stabilized cation, then one obtains a dipolar carbene (2) which can also be regarded as allene (3). We have now found that such donor/acceptor-substituted allenes are likewise ambiphilic, i. e. can react at the central atom C2 both electrophilically as well as nucleophilically.…”
Section: By Rolf W Saalfrank Winjiiied Paul and Heide Liebenow"'mentioning
confidence: 99%